Ratiometric Sensing of Azithromycin and Sulfide Using Dual Emissive Carbon Dots: A Turn On-Off-On Approach - Mahmoud, Ashraf M.; Alqahtani, Yahya S.; El-Wekil, Mohamed M.; Ali, Al-Montaser Bellah H. (Journal of fluorescence, 2025)
A novel ratiometric fluorescence probe was developed for the determination of azithromycin (AZM) and sulfide ions based on the differential modulation of red emissive carbon dots (R-N@CDs) and blue emissive carbon dots (B-NS@CDs). The addition of sulfide anion selectively quenched the red emission of R-N@CDs while the blue emission of B-NS@CDs unaffected. Upon subsequent introduction of AZM to this R-N@CDs@sulfide system, the quenched red fluorescence was restored. Comprehensive characterization of the CDs was performed using UV-Vis, fluorescence, FTIR spectroscopy, XPS, and TEM. The proposed method exhibited excellent sensitivity and selectivity, with limits of detection of 0.33 µM for AZM and 0.21 µM for sulfide. Notably, this approach enabled direct detection of sulfide without requiring prior modulation of the CDs with metal ions, as is common in other reported methods. The ratiometric probe was successfully applied for the determination of AZM in biological fluids and sulfide in environmental water samples with high selectivity. This work presents the first fluorometric method for the detection of AZM in biological fluids.